Phytoremediation of Acid Mine Drainage with Melaleuca cajuputi, Nauclea orientalis, and Vetiveria zizanioides in Floating Treatment Wetland - Fitri Arum Sekarjannah; Irdika Mansur; Zaenal Abidin; Anas Miftah Fauzi (HAYATI Journal of Biosciences, 2023)
The formation of acid mine drainage (AMD) is a common environmental problem in the mining industry. Its passive management through wetland construction has gained more consideration in recent years. However, the application in the field is constrained by the large area and relatively shallow depth. Indonesia has no passive technology to neutralize AMD in deep water. One solution is to apply a floating treatment wetland (FTW) system. Therefore, this study aimed to determine the ability of several hyperaccumulator plants, such as Melaleuca cajuputi, Nauclea orientalis, and Vetiveria zizanioides, to neutralize AMD using a floating system by conducting FTW trials. The method used was a Completely Randomized Design (CRD) with 3 treatments and control/without plants. Each treatment had 3 replications, resulting in 12 experimental units. The results showed that the FTW with or without plants could increase pH and decrease dissolved Mn by 75.31-90.74%. Heavy metals were chelated by organic matter, absorbed by plants, and deposited in the form of metal sulfides. The results also indicated that besides having a positive effect on pH and heavy metal reduction, the organic-based floating wetland increased biological oxygen demand (BOD) from 61.08-79.71%.